2010
DOI: 10.1128/iai.00963-09
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoke Exposure Impairs Pulmonary Bacterial Clearance and Alveolar Macrophage Complement-Mediated Phagocytosis of Streptococcus pneumoniae

Abstract: Cigarette smoke exposure increases the risk of pulmonary and invasive infections caused by Streptococcus pneumoniae, the most commonly isolated organism from patients with community-acquired pneumonia. Despite this association, the mechanisms by which cigarette smoke exposure diminishes host defense against S. pneumoniae infections are poorly understood. In this study, we compared the responses of BALB/c mice following an intratracheal challenge with S. pneumoniae after 5 weeks of exposure to room air or cigar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
90
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(96 citation statements)
references
References 38 publications
2
90
1
3
Order By: Relevance
“…increased pulmonary bacterial burden, and worsened clinical signs of pneumococcal pneumonia (42). Our investigations suggest the possibility that cigarette smoke exposure results in a baseline increase in the proinflammatory state of the lung.…”
Section: Discussionmentioning
confidence: 72%
“…increased pulmonary bacterial burden, and worsened clinical signs of pneumococcal pneumonia (42). Our investigations suggest the possibility that cigarette smoke exposure results in a baseline increase in the proinflammatory state of the lung.…”
Section: Discussionmentioning
confidence: 72%
“…Cigarette smoke exerts damaging and proinflammatory effects in the lungs but also can directly suppress innate and adaptive immune processes (7)(8)(9)(10). Studies in animal models have demonstrated that exposure to cigarette smoke exacerbates inflammatory responses elicited by several different bacterial agents, including nontypeable Haemophilus influenzae (NTHi), Pseudomonas aeruginosa, and Streptococcus pneumonia (11)(12)(13)(14). In all studies, the cellular composition of the bacteria-exacerbated inflammatory response was neutrophilic in nature.…”
mentioning
confidence: 91%
“…Smoke also seems to exacerbate the impairment in mucociliary clearance of S. pneumoniae induced by the ingestion of ethanol [94]. Cigarette smoke has been shown to prevent complement-mediated phagocytosis of S. pneumoniae by alveolar macrophages, while the ingestion of unopsonised bacteria or IgG-coated microspheres is not affected, thus impairing pulmonary bacterial clearance [95].…”
Section: The Vicious Circle Hypothesismentioning
confidence: 99%